Discovery of Aphanipathes verticillata (Cnidaria: Anthozoa: Antipatharia) in the Hawaiian Islands - Opresko, D. M.; Wagner, D.; Montgomery, A. D.; Brugler, M. R. (Zootaxa, 2012)
Mesophotic coral reef surveys conducted off Maui in 2008–2009 revealed several specimens superficially resembling thecommercial black coral species Antipathes griggi Opresko 2009. After subsequent microscopic examination of the skel-etal features, these colonies proved to be morphologically very similar to Aphanipathes verticillata Brook 1889, a speciesnever before reported from the Hawaiian Islands. A comparison with samples of the type material of A. verticillata indi-cated that the specimens collected in Hawaiian waters differed from the type in having simplier and less dense tubercleson the skeletal spines, a character which merits the recognition of the Hawaiian population as a new subspecies, A. ver-ticillata mauiensis. Colonies of the new subspecies exhibit considerable morphological variation; DNA analysis of fifteenspecimens ruled out the possibility of the presence of a cryptic species. Further DNA investigations on specimens fromvarious localities in the western Pacific and Indian Ocean are needed to better understand the genetic relationship betweenthe two forms. The morphological similarity of A. verticillata mauiensis with Antipathes griggi raises questions concern-ing the validity of past field surveys evaluating the population size and structure of A. griggi since it is possible that thetwo species could easily be misidentified based on gross morphology alone. Additional studies are also needed to document the geographic and bathymetric distribution of the subspecies along the Hawaiian Island chain.